2008
DOI: 10.1063/1.2885080
|View full text |Cite
|
Sign up to set email alerts
|

Photoemission and x-ray absorption studies of valence states in (Ni,Zn,Fe,Ti)3O4 thin films exhibiting photoinduced magnetization

Abstract: By means of photoemission and x-ray absorption spectroscopy, we have studied the electronic structure of (Ni,Zn,Fe,Ti)3O4 thin films, which exhibits a cluster glass behavior with a spin-freezing temperature Tf of ∼230K and photoinduced magnetization (PIM) below Tf. The Ni and Zn ions were found to be in the divalent states. Most of the Fe and Ti ions in the thin films were trivalent (Fe3+) and tetravalent (Ti4+), respectively. While Ti doping did not affect the valence states of the Ni and Zn ions, a small amo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…It can be seen that the lattice parameter a increases from 8.35 Å when x = 0.00 to 8.40 Å when x = 0.312, which cannot be explained if Ti ions are assumed to be in the Ti 4+ form , due to the effective radius of Ti 4+ (0.605 Å) being smaller than that of Fe 2+ (0.78 Å) and Ni 2+ (0.69 Å), with the coordination number 6 .…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…It can be seen that the lattice parameter a increases from 8.35 Å when x = 0.00 to 8.40 Å when x = 0.312, which cannot be explained if Ti ions are assumed to be in the Ti 4+ form , due to the effective radius of Ti 4+ (0.605 Å) being smaller than that of Fe 2+ (0.78 Å) and Ni 2+ (0.69 Å), with the coordination number 6 .…”
Section: Resultsmentioning
confidence: 91%
“…Many reports have assumed that Ti cations appear in the form Ti 4+ in ferrites according to the traditional views . Kale et al prepared Ni 1+ x Ti x Fe 2−2 x O 4 (0 ≤ x ≤ 0.7) polycrystalline samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Srivastava et al [7] studied Ni 0.7+x Zn 0.3 Ti x Fe 2À2x O 4 (0 6 x 6 0.08) samples, and considered that all Ti 4+ cations entered [B] sites, with the result that a canted spin structure arose. Kobayashi et al [8] produced Ni 0.4+x Zn 0.6Àx Ti x Fe 2Àx O 4 (0 6 x 6 0.3) films, and concluded that most Ti ions in the samples were Ti 4+ cations, with a small amount of Ti 3+ . Dwivedi et al [9] prepared CoTi 2x Fe 2À2x O 4 (x = 0.0, 0.05, and 0.1) powder samples, and found that the saturation magnetization of the samples decreased with increasing Ti doping level.…”
Section: Introductionmentioning
confidence: 98%
“…To date, it has been assumed that Ti cations in ferrites are in the form of Ti 4+ ions and that they have no magnetic moment [6][7][8][9][10][11][12]. Jin et al [6] prepared Fe 3Àx Ti x O 4 (0 6 x 6 0.09) films on (0 0 1) oriented MgO substrates.…”
Section: Introductionmentioning
confidence: 99%